Pulmonary transport and deposition of inhaled particles - Miguel, Antonio F. (2016)
Breathing is the way that the respiratory tree interacts with the outside environment. The large surface area of tree available for gas exchange is also exposed to particles suspended in the inhaled air. A two-fold justification exists for studying particle transport and deposition in the respiratory tree.This study offers a spatial accurate analysis that gives us insight into the particle dynamics under steady and pulsatile flow fields in the bronchial tree.